The Effect of Deposition Rate on the Electrical Properties of Indium Tin Oxide (ITO) Thin Films - Hadaate Ullah; Shahin Mahmud; Fahmida Sharmin Jui (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Indium-tin oxide (ITO) which is optically transparent is referred as a “universal” electrode for various optoelectronic devices such as organic light emitting diodes (OLEDs). It is scientifically proved that the performance of OLEDs raises up significantly by exposing the ITO surface to oxygen plasma. This study employs conducting atomic force microscopy (C-AFM) for unique nanometer-scale mapping of the local current density of a vapor-deposited ITO film. Indium Tin Oxide (ITO) thin films have been prepared by using the reactive evaporation method on glass substrates in an oxygen atmosphere. It is found that the deposition rate plays a vital role in controlling the electrical properties of the ITO thin films. The resistivity and the electrical conductivity were also investigated. The electrical resistivity of 3.10 x10 –6 Ωm has been obtained with a deposition rate of 2 nm/min.